Immediate sequential bilateral cataract surgery is a reasonable and safe option during a pandemic - Ece, Berire Şeyma Durmuş; Özgür, Armağan; Işık, Mehmet Uğur; Furuncuoğlu, Utku; İlgüy, Serdar; Yüksel, Erdem (Elsevier BV, 2023)
To evaluate the preoperative and intraoperative features, intraoperative and postoperative complications and postoperative satisfaction of patients who underwent immediate sequential bilateral cataract surgery (ISBCS) during the COVID-19 pandemic.The study included ISBCS patients from September 2021 through January 2022. Demographics, comorbidities, type of anesthesia (topical/general), intraoperative complications, postoperative refractive errors, and complications were examined. The one-month postoperative appointment included a patient satisfaction questionnaire.ISBCS was performed in 206 eyes of 103 patients. Intraoperative complications did not occur in 99 (96.1%) of ISBCS patients. No patients had visually significant corneal edema, wound leakage, endophthalmitis, or toxic anterior segment syndrome during postoperative follow-up. Final manifest spherical equivalent refraction was less than 1.00 D in all patients and less than 0.50 D in 70.7% of patients. In the questionnaire given to the patients at the one-month follow-up, 96.1% of patients did not change their preference for surgery on the same day.ISBCS provides an advantage during the pandemic period by reducing hospital visits, especially for the elderly population and patients with comorbidities. ISBCS is a safe and reasonable method that can be used during a pandemic due to the low rates of complications, the success of the refractive results, and the high patient satisfaction rates.
Keywords: Phacoemulsification; Postoperative Complications; Lens Implantation, Intraocular; Visual Acuity; Humans; COVID-19; Original Article; Cataract Extraction; Pandemics; Cataract; Aged; Retrospective Studies; 3. Good health